2010
DOI: 10.1002/ieam.141
|View full text |Cite
|
Sign up to set email alerts
|

Field sensitivity distribution of macroinvertebrates for phosphorus in inland waters

Abstract: The magnitude of ecological damage caused by elevated phosphorus concentrations in Dutch inland waters was evaluated and expressed as the fraction of disappeared genera. We used national abundance data stored in the Limnodata Neerlandica from 1980 until 2005. We derived the presence or absence in the concentration range between 0.001 and 40 mg/l total phosphorus for 867 macro-invertebrate genera. At concentrations above 0.1 mg/l, which is considered a signal of nutrient enrichment of freshwater, the fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
(19 reference statements)
1
34
0
3
Order By: Relevance
“…This suggests that the total P is a better indicator of the stream health than the total N, which is greatly influenced by the stream section. The forward selection showed that the total N was not a significant factor, contrary to the total P, which has a strong influence on the structure of the caddisfly assemblage, which was also confirmed by other authors (Struijs et al, 2011). However, the number of caddisfly species decreases when at least one of these two nutrients is high (such as at locality 1).…”
Section: Figuresupporting
confidence: 76%
“…This suggests that the total P is a better indicator of the stream health than the total N, which is greatly influenced by the stream section. The forward selection showed that the total N was not a significant factor, contrary to the total P, which has a strong influence on the structure of the caddisfly assemblage, which was also confirmed by other authors (Struijs et al, 2011). However, the number of caddisfly species decreases when at least one of these two nutrients is high (such as at locality 1).…”
Section: Figuresupporting
confidence: 76%
“…Many studies have focused on the effects of increasing P 65 in one or more specific water bodies, species, or regions (Dodson et al, 2000;Smith et al, 66 2007; Struijs et al, 2011b). However, to our knowledge, no study has outlined the effects of 67 different P concentrations on relative species richness on a global scale.…”
Section: Introduction 50mentioning
confidence: 99%
“…104 This approach has been applied by Struijs et al (2011b) relative species richness (eRSR) of species in group g at concentration C i in freshwater type t 114 in region h. At C opt , eRSR is one. Conversely, an eRSR of zero represents the complete 115 absence of species.…”
Section: Introduction 50mentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to accept the limitations of field data for reasons of data availability, as laboratory data for temperature tolerance were available for only six mollusc species and several species groups (e.g., Sphaeriidae and Unionidae) are only rarely the subject of physiological research. Moreover, other authors suggest that tolerance levels derived from field data may be more environmentally relevant and realistic than reference levels obtained in laboratory tests (Kwok et al 2008;Leung et al 2005;Struijs et al 2011). …”
mentioning
confidence: 99%